Una aproximación a la intervención del Trabajo Social comunitario en situaciones de catástrofes y desastres - COLOMA PEÑATE, África (Cuadernos de Trabajo Social, 2009)
The objective of this article is to expose the general research lines drawn in the investigation which attended to make an approach to the «Community Social Work intervention in Catastrophes and disasters». The tools that were proposed for that approximation were: a) the knowledge of the «intervention models» use in these situations; b) social workers’ main lines of action; c) required knowledge; d) the main challenges that Social Work has to face in order to consolidate and expand its space in this field of intervention. In order to develop qualitative investigation 12 semi-structured interviews were required to professional experts in this area of intervention, mainly social workers. This article presents the results and conclusions of such approximation.